Targeted nanoparticle delivery unleashes synergistic photothermal and immunotherapeutic effects against hepatocellular carcinoma - Amal Babu; Sathiyamoorthy Padmanaban; Sahil Chahal; Adityanarayan Mohapatra; Aravindkumar Sundaram; Chong-Su Cho; In-Kyu Park (Journal of Nanobiotechnology)
Abstract The substantial mortality and morbidity of hepatocellular carcinoma, representing 90% of liver cancers, poses a significant health burden. The effectiveness of traditional hepatocellular carcinoma treatments such as surgical resection, radiotherapy, and chemotherapy is limited, underscoring the need for innovative therapeutic strategies. To this end, we synthesized phthalyl-pullulan nanoparticles encapsulating IR780 (an NIR-responsive heptamethine cyanine dye) and R848 (resiquimod; a TLR7/8 agonist) (PIR NPs). Characterization confirmed the size and loading capacity of PIR NPs, and controlled release of R848 therefrom upon NIR irradiation, thereby establishing the potential of this versatile therapeutic tool. PIR NPs were readily taken up by Hepa 1–6 cells in vitro by targeting asialoglycoprotein receptors present on its cellular surface. In in vivo experiments combining photothermal therapy and immunotherapy, following the local near-infrared irradiation, the PIR NPs accumulated in tumor sites induced immunogenic cell death and activated a tumor-specific T-cell immune response, thus highlighting their potent antitumor efficacy. The combined efficacy of photothermal therapy and immunotherapy presents a promising avenue for addressing the shortcomings of traditional hepatocellular carcinoma interventions. This study contributes valuable insights into the development of more effective and targeted therapeutic approaches for hepatocellular carcinoma treatment. Graphical abstract